Great Britain miscellany - Great Britain
Deeds, agreements, marriage settlements, and other records.
Collection material in English and Latin.
Keywords: Deeds -- Great Britain; Marriage records -- Great Britain; Great Britain -- Genealogy; Great Britain -- History